PREPARING A PRESCHOOL CHILD FOR SCHOOL EDUCATION BASED ON PSYCHOLOGICAL APPROACHES - Nigora Shamsutdinovna Gaziyeva (Web of Journals Publishing, 2024)
This article explores the psychological approaches to preparing preschool children for school education. It discusses the significance of early childhood development, the role of psychological readiness, and the application of modern methodologies in fostering cognitive, emotional, and social competencies in young learners. The article emphasizes the need for a balanced approach that aligns the developmental needs of children with the expectations of formal schooling, ensuring a smoother transition and a positive learning experience
Keywords: preschool education, school readiness, psychological approaches, early childhood development, cognitive skills, emotional readiness.